2009
DOI: 10.1104/pp.108.133454
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tolerance to Chilling Stress in OsMYB3R-2 Transgenic Rice Is Mediated by Alteration in Cell Cycle and Ectopic Expression of Stress Genes    

Abstract: MYB transcription factors play central roles in plant responses to abiotic stresses. How stress affects development is poorly understood. Here, we show that OsMYB3R-2 functions in both stress and developmental processes in rice (Oryza sativa). Transgenic plants overexpressing OsMYB3R-2 exhibited enhanced cold tolerance. Cold treatment greatly induced the expression of OsMYB3R-2, which encodes an active transcription factor. We show that OsMYB3R-2 specifically bound to a mitosis-specific activator cis-element, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(216 citation statements)
references
References 70 publications
(115 reference statements)
8
207
0
1
Order By: Relevance
“…Overexpression of DRE-B1A/CBF3 induces DREB1, DREB2, and RD29A genes and confers increased resistance to drought, high-salt, and freezing stresses [41]. Although OE-OsMYB3R-2 exhibited enhanced cold tolerance in rice, it also resulted in growth retardation under normal conditions [42]. Similarly, OE-DREB1A in Arabidopsis caused severe growth retardation [41], and overexpression of CBF1 in tomato resulted in a dwarf phenotype [43].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DRE-B1A/CBF3 induces DREB1, DREB2, and RD29A genes and confers increased resistance to drought, high-salt, and freezing stresses [41]. Although OE-OsMYB3R-2 exhibited enhanced cold tolerance in rice, it also resulted in growth retardation under normal conditions [42]. Similarly, OE-DREB1A in Arabidopsis caused severe growth retardation [41], and overexpression of CBF1 in tomato resulted in a dwarf phenotype [43].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, overexpression of OsMYB4 significantly enhanced tolerance to chilling and freezing stress in transgenic Arabidopsis (Vannini et al 2004;Pasquali et al 2008). Ma et al (2009) reported that OsMYB3R-2 participated in cold signalling pathway by targeting the cell cycle and a putative DREB/CBF. Moreover, a recent study revealed that OsMYBS3 was essential for conferring tolerance to cold stress in rice plants (Su et al 2010) while R2R3MYB gene, OsMYB2, was involved in salt, cold, and dehydration tolerance in rice ).…”
Section: Abiotic Stressmentioning
confidence: 99%
“…Furthermore, many of the genes in the ATTED coexpression clusters of these genes are coordinately upregulated (see Supplemental Figure 14 and Supplemental Table 3 online), suggesting that plants either experience stress by RBR downregulation or that a general stress signaling pathway is attenuated by RBR and becomes deregulated by small changes in RBR activity. Links between cell cycle responses and different stresses have been made for plants (Ma et al, 2009) and animal cells (Burhans and Heintz, 2009;Mavrogonatou and Kletsas, 2009), but the mechanisms underlying the crosstalk between cell cycle and stresses remain unknown.…”
Section: Gene Expression Regulation By Rbrmentioning
confidence: 99%